Synthesis and Characterization of Nano Active Filler of Pumice Particle Produced by Sol-Gel Process with Different Precipitation Temperatures for Enhancing the Impact Properties of GFRP Composite - Diharjo, Kuncoro; Rakhman, Andry; Raharjo, Wijang Wisnu; Suryanti, Venty; Kaleg, Sunarto (Applied Science and Engineering Progress, 2025)
Pumice, a volcanic mineral abundant in Indonesia that can contain up to 70% silica, is a great source of nanosilica material. The mesoporous amorphous nanosilica, called nano active filler of pumice particle (nAFPP), has been successfully synthesized using a sol-gel process with different precipitation temperatures at 45, 55, and 65 °C. The nAFPP was characterized using SEM-EDX, Multi-Point BET, and BJH techniques for surface properties and morphologies studies, FTIR for chemical bond studies, XRD for crystallinity properties, and TGA/DTA characterization for thermal stability studies. The influence of nanosilica filler in forming GFRP/nAFPP composites was evaluated using impact testing and morphological analysis with SEM on the fracture surfaces. The result shows that the nanosilica of nAFPP has good purity (93.68%), mesoporous amorphous, nano-sized silica particles, and a pore diameter of 4.36–6.97 nm. The spectra of FTIR display the absorption peaks of the functional group silanol (Si-O-Si). The GFRP/nAFPP composites have higher impact strength than those with pumice particles or without particles. The highest impact strength (97.37 KJ/m2) is achieved in the GFRP composite with 2.5 of nAFPPP, and its addition until 10 decreases the impact strength slightly. Further research on this material is needed to accelerate its application.